Does aspirin really reduce the colorectal cancer risk? - Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2013)
Journal of Advances in Internal Medicine 2013;02(01):1-2 DOI: http://dx.doi.org/10.3126/jaim.v2i1.7627